Formulation of a baby food from mung bean flour (Phaseolus aureus Roxb.) and carrots (Daucus carota Linn.) - Evangelista, Milda E.; Acevedo, Teresita P. (1973)
The study involved the formulation of a baby food based on mung bean flour and carrot puree. Based on the computation of the lethality and microbiological examination, the product was found to be commercially sterile after processing for one hour at 250°F. The physico-chemical tests and organoleptic evaluation revealed that the product was moderately acceptable.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Mung bean flour; Carrots; Baby foods